1989
DOI: 10.1677/joe.0.120r015
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Growth Hormone Activity in Sheep Using McNcclcnal Antibodies

Abstract: Monoclonal antibody OA11 was raised against ovine GH; its effects on GH activity were examined in a target species relevant for animal production in vivo. The monoclonal antibody was found to enhance the galactopoietic response to exogenous GH in adult lactating ewes and also to potentiate the diabetogenic activity of both exogenous and endogenous GH in ewe lambs. Thus it was shown that GH activity may be manipulated above its usual dose-response range in normal, intact animals of commercial importance via imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…[8][9][10][11][12][13] Here, we show that antibody buffering can occur in a different body compartment, the CSF. Using a small molecule ligand, 2-phenyl-oxazol-5-one-methylene-γ-amino butyrate, we demonstrate that antibody buffering can extend the pharmacokinetic profile of a drug in the rat cerebrospinal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Here, we show that antibody buffering can occur in a different body compartment, the CSF. Using a small molecule ligand, 2-phenyl-oxazol-5-one-methylene-γ-amino butyrate, we demonstrate that antibody buffering can extend the pharmacokinetic profile of a drug in the rat cerebrospinal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…An enhancing effect on gonadotropin activity was described in vivo in Snell dwarf mice using the uterine weight bioassay, with polyclonal Abs directed against the β-subunit of ovine FSH [95] and monoclonal Abs directed against bovine FSH [96]. Likewise, anti-GH [97] and anti-TSH [98] monoclonal Abs exhibiting enhanced bioactivity both in vitro and in vivo when complexed with their cognate hormone have been described [99,100]. More recently, Boyman et al have demonstrated the enhancing effect of IL/anti-IL Ab complexes (IL-2 and IL-7) in cancer treatment [101,102].…”
Section: Enhancing Antibodies Complexed With Gonadotropins As Biased mentioning
confidence: 99%
“…Indeed, peripherally administered therapeutic antibodies against amyloid ␤-peptide are found in the central nervous system (8) and enhancing antibodies to porcine growth hormone (GH) change the distribution of tissue GH (107,114). An intriguing observation in antibody enhancement of peptide hormone activity is that only a proportion of exogenous hormone needs be complexed to antibody for potentiation to occur (51,88).…”
Section: Identifying Important Parameters Of Antibody Interactions Inmentioning
confidence: 99%